p-ADIC EISENSTEIN SERIES AND L-FUNCTIONS OF CERTAIN CUSP FORMS ON DEFINITE UNITARY GROUPS. (21st November 2014) - Eischen, Ellen; Wan, Xin
Abstract : We construct p -adic families of Klingen–Eisenstein series and L -functions for cusp forms (not necessarily ordinary) unramified at an odd prime p on definite unitary groups of signature (r, 0) (for any positive integer r ) for a quadratic imaginary field K split at p . When r=2, we show that the constant term of the Klingen–Eisenstein family is divisible by a certain p -adic L -function.